Investigation on the ultrasonic propagation mechanism and its application on air-source heat pump defrosting. (25th August 2016) - Tan, Haihui; Xu, Guanghua; Tao, Tangfei; Zhang, Sicong; Luo, Ailing
Highlights: Optimal defrosting mode for finned-tube evaporator is S0 mode. Stress excited by ultrasonic vibration is larger than ice adhesion stress 0.4 MPa. Frequency matching can enhance the defrosting efficiency effectively. Ultrasonic vibration can effectively suppressing the frost deposition. Thermal comfort and heat transfer efficiency enhanced with ultrasonic vibration. Abstract: Frosting deposited on the outdoor coil of air-source heat pump (ASHP) units deteriorates the operational performance and energy efficiency. Therefore, periodic defrosting is necessary. First, the dispersion curves for the propagation mechanism of an ultrasonic guided wave in the evaporator are determined through numerical calculation. In addition, the shear stress and vibration characteristics under ultrasonic excitation are analysed using finite element method (FEM). Finally, the vibration amplitude and defrosting performance of ultrasonic vibration is analysed. The numerical calculation results indicate that three guided wave modes exist in the evaporator, including both A0 and S0 modes of the Lamb wave and SH0 mode of the SH wave, with the optimal defrosting mode being S0 of the Lamb wave. The FEM results show that the vibrational shapes of S0 mode and longitudinal mode clearly exists in the fin and tube, the torsional and flexural modes also exist in the tube, and the FEM results are consistent with the numerical calculation results. The impedance analysis and laser vibrometer results indicate that the resonance frequency shifting, electro-acoustic converting efficiency and vibration energy decrease is due to increasing external load. The ultrasonic defrosting experimental results indicate that ultrasonic vibration can suppress frost deposit on the fin surface.